The sickness unto death : a Christian psychological exposition for upbuilding and awakening - Kierkegaard, Søren, 1813-1855 (Kierkegaard, Søren, 1813-1855. Works. 1978 ;, 1980)
"A companion piece to 'The Concept of Anxiety', this work continues Søren Kierkegaard's radical and comprehensive analysis of human nature in a spectrum of possibilities of existence. Present here is a remarkable combination of the insight of the poet and the contemplation of the philosopher. In 'The Sickeness unto Death', Kierkegaard moves beyond anxiety on the mental-emotional level to the spiritual level, where, in contact with the eternal, anxiety becomes despair. Both anxiety and despair reflect the misrelation that arises in the self when the elements of the synthesis - the infinite and the finite - do not come into proper relation to each other. Despair is a deeper expression for anxiety and is a mark of the eternal, which is intended to penetrate temporal existence." -- BOOK JACKET.